Neonatal cardiorespiratory failure caused by splenic hemorrhages: a case report on a fatal and a rescued case - Nadieh A. Jansen; Anne T M Dittrich; Manouk Backes; Benno Kusters; Willemijn M Klein; Tim Hundscheid (BMC, 2024)
Abstract Two cases of neonatal splenic hemorrhage with acute cardiorespiratory failure are described in this report. The first case involves a full-term neonate who was found unresponsive without any witnesses and could not be successfully resuscitated. A postmortem diagnosis revealed a splenic hemorrhage. Second case is an extremely premature neonate who experienced a witnessed cardiovascular collapse on the 14th day of life. Rapid cardiovascular support was administered, resulting in a positive outcome. While splenic hemorrhage is commonly associated with traumatic events, these cases highlight the need of considering spontaneous splenic hemorrhages as a potential cause of acute neonatal compromise, even in the absence of birth-related trauma (e.g., asphyxia, prolonged labor, clavicle fractures, brachial plexus injuries). This report emphasizes the importance of including splenic hemorrhage timely in the differential diagnosis of neonatal cardiorespiratory instability, especially in the absence of more common diagnoses, and discusses the challenges associated with its recognition and treatment.